Effect of cobalt carboxylate on thermal degradation of polyethylene (HDPE) - Norshafika, Yahya (2010)
This study reports the effect of cobalt carboxylate on thermal degradation of polyethylene (HDPE). The purpose of this study is to gain knowledge and understand behaviour of HDPE film after adding cobalt carboxylate as additive after and before expose to the heating in the oven at 600C and also to investigate characteristics of cobalt carboxylate itself. The additives used were three cobalt carboxylate which are cobalt stearate, cobalt palmitate, and cobalt laurate and thin film HDPE containing these additives were prepared with different concentration (0.2% w/w, 0.5% w/w, and 1.0% w/w) by sheeting process. Seventy micron film of HDPE containing different concentration of additives and 3 types of cobalt carboxylate were subsequently exposed to heat and were observed. The characteristics of cobalt carboxylate were monitor by measuring the temperature degradation using TGA (Thermal Gravimetric Analyzer) and to measuring melting point using DSC (Different Scanning Calorimeter). While, the degradation was monitored by measuring the elongation break using tensile machine, changes of structure peak using FTIR and surface film using SEM. In DSC and TGA result, found that, cobalt stearate has high temperature of degradation and high melting point at 121.970C; 309.80C followed by cobalt palmitate and cobalt laurate at 84.060C; 282.740C and 69.040C; 182.970C, respectively. While for FTIR result, Carbonyl Index (CI), which in turn leads to an increase according to the increase of concentration of additives especially cobalt stearate and for tensile test, the percent of break strain decreased inversely proportional with increasing concentration additive present. Results on mechanical properties reveal that samples containing cobalt carboxylate, become mechanically fragile, embrittlement and flaking occurred for samples exposed to longer time periods in the oven for 480 hours. The effect of cobalt carboxylate on air oven aging, show that different behaviour of HDPE at different concentrations will increase proportionally with increasing chain length and follows order CoSt3>CoPal3>CoLau3